Faster cytotoxicity with age: Increased perforin and granzyme levels in cytotoxic CD8+ T cells boost cancer cell elimination. Issue 8 (11th July 2022) - Zöphel, Dorina; Angenendt, Adrian; Kaschek, Lea; Ravichandran, Keerthana; Hof, Chantal; Janku, Sandra; Hoth, Markus; Lis, Annette
Abstract: A variety of intrinsic and extrinsic factors contribute to the altered efficiency of CTLs in elderly organisms. In particular, the efficacy of antiviral CD8 + T cells responses in the elderly has come back into focus since the COVID‐19 pandemic outbreak. However, the exact molecular mechanisms leading to alterations in T cell function and the origin of the observed impairments have not been fully explored. Therefore, we investigated whether intrinsic changes affect the cytotoxic ability of CD8 + T cells in aging. We focused on the different subpopulations and time‐resolved quantification of cytotoxicity during tumor cell elimination. We report a surprising result: Killing kinetics of CD8 + T cells from elderly mice are much faster than those of CD8 + T cells from adult mice. This is true not only in the total CD8 + T cell population but also for their effector (TEM ) and central memory (TCM ) T cell subpopulations. TIRF experiments reveal that CD8 + T cells from elderly mice possess comparable numbers of fusion events per cell, but significantly increased numbers of cells with granule fusion. Analysis of the cytotoxic granule (CG) content shows significantly increased perforin and granzyme levels and turns CD8 + T cells of elderly mice into very efficient killers. This highlights the importance of distinguishing between cell‐intrinsic alterations and microenvironmental changes in elderly individuals. Our results also stress the importance of analyzing the dynamics of CTL cytotoxicity against cancer cells because, with a simple endpoint lysis analysis, cytotoxic differences could have easily been overlooked. Abstract : Immunosenescence is associated with decreased T cell numbers and impaired functionality of cytotoxic T lymphocytes (CTL). Surprisingly, we find that, despite immunosenescence, CTL efficiency against cancer cells increases with age, if similar CTL numbers or individual cells are compared. Elevated perforin and granzyme levels turn CTLs of elderly mice into ultimate killers, highlighting the importance of distinguishing cell intrinsic alterations from microenvironmental changes in elderly individuals.